(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Women constitute half of the population and contribute much share for social and economic development of society. In spite of this fact, they are most excluded group from mainstream occupation and majority of them are engaged in the informal sector. The informal economy constitute informal (unorganized) sector and its workers plus the informal workers in the formal sector constitute the informal economy. To know the problem of brick kiln workers, the study is carried out in Jhajjar district of Haryana. It is found that women play an important role in economic activity of family but this fact is not acknowledged by their family members. Women do not receive wages of work performed by them and wages are collected by their husbands. Main problem of the backwardness of women workers is low level of education. There is no facility of education at the kiln. Education can play an important role to improve the position of brick kiln workers, so the government should give more focus on education of women and the children of workers at the kiln.